Preparation method and application of heat-insulating and flame-retardant silicon-based composite aerogel
The silicon-based composite aerogel modified by cellulose nanofibrils/graphene oxide solves the problem of balancing flame retardancy and mechanical properties of silicon-based aerogel and achieves high thermal insulation, flame retardancy and mechanical properties. It is suitable for the field of building insulation.
Patent Information
- Application Number
- CN202411228938.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-01-24
AI Technical Summary
Silicon-based aerogel materials are difficult to balance between flame retardant properties and mechanical properties, and the preparation process is complex, which limits their wide application in the field of building insulation.
By co-grinding cellulose nanofibrils with graphene oxide to form modified nanofillers, and combining them with silane coupling agents, through specific process steps such as stirring, ultrasonic treatment and solvent replacement washing, a nanofiber with excellent barrier properties was prepared. Silicone-based composite aerogels with thermal, flame retardant and mechanical properties.
It achieves a balance between the flame retardant performance and mechanical properties of silicon-based airgel, improves its thermal insulation performance and stability, and is suitable for the field of building insulation.
Smart Images

Figure CN119349979A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer materials, and in particular to a preparation method and application of a heat-insulating and flame-retardant silicon-based composite aerogel. Background Art
[0002] The demand for building insulation materials in modern society is growing exponentially every year, reaching about 23 billion square meters in 2022 alone. Organic insulation materials are widely used in the fields of insulation and heat insulation due to their advantages such as light weight, low thermal conductivity and easy molding. However, traditional organic insulation materials are mainly fossil materials such as extruded polystyrene boards, foamed polystyrene boards, and polyurethane foams. Their production and processing processes are energy-intensive and not easy to degrade, which brings huge energy and environmental pressures to society. At the same time, traditional organic insulation materials are often easy to burn and release a large amount of toxic gases during the combustion process, causing a lot of economic losses (my country's direct losses in 2022 were 5.85 billion yuan) and casualties; although inorganic materials have good thermal stability, they have problems such as toxicity and carcinogenicity. Therefore, silica-based aerogels with nanoporous structures are considered to be the most promising candidates for green flame retardant materials. However, the structure of silica-based aerogels themselves is inherently brittle, and the low mechanical strength limits its practical application. Current research shows that using fiber materials to enhance their mechanical properties is an effective method.
[0003] The patent specification with the authorization number CN111560172B discloses a method for preparing a biomass fiber reinforced organosilicon aerogel material, by laying biomass fibers in a mold, injecting the precursor sol of organosilicon aerogel, and then obtaining a biomass fiber composite aerogel with excellent thermal insulation performance and flexibility through supercritical drying technology. The patent specification with the publication number CN108641361A discloses a method for preparing a fiber-reinforced organosilicon aerogel thermal insulation composite material, using a porous siloxane polymer as a matrix, adding a flexible fiber felt, preparing an organosilicon solution, impregnating the flexible fiber felt with the solution, and then undergoing sol-gel, washing-drying to finally obtain an organosilicon aerogel composite material with excellent thermal insulation performance. However, the above-prepared aerogel and its composite material do not have good flame retardant properties due to the presence of a large number of organic groups on their silane molecules, and the objects added or modified are mostly flammable materials. If applied to the field of building insulation, it may bring huge fire hazards.
[0004] In order to solve the problem of poor flame retardancy of silicon-based aerogels, the patent specification with the authorization number CN110127705B discloses a method for preparing flame-retardant silicon-based aerogels modified with graphene oxide. The graphene oxide material and silicon dioxide are cross-linked through a special strip-shaped network structure to prepare silicon-based aerogels with good flame retardancy. However, due to the weak interaction between the graphene oxide sheets and the organic silicon molecular chains inside the obtained aerogel, its mechanical properties still have room for further improvement.
[0005] In summary, although the research on silicon-based aerogel materials has made remarkable progress, there are still problems such as complex preparation process (supercritical drying) and imbalance between performance parameters (flame retardant and mechanical properties are difficult to take into account), which greatly restricts its further application and development. Therefore, designing and developing a type of silicon-based composite aerogel with simple preparation process / flame retardant and mechanical properties is a technical problem that needs to be solved urgently by technicians in this field. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the present application provides a method for preparing a thermally insulating and flame-retardant silicon-based composite aerogel by modifying cellulose nanofibrils / graphene oxide so as to have more ideal thermal insulating and flame-retardant properties.
[0007] In order to achieve the above-mentioned purpose, the technical solution of the present application is as follows: a method for preparing a heat-insulating flame-retardant silicon-based composite aerogel, the specific steps of the method comprising:
[0008] (1) mixing a silane coupling agent, an acid catalyst, a surfactant, a co-solvent and water, adjusting the pH to 2 to 5, stirring and hydrolyzing to obtain a silica sol solution;
[0009] (2) adding an alkali catalyst to the obtained silica sol solution, stirring, adjusting the pH to 9-11, adding a cellulose nanofibril / graphene oxide co-grinding solution, stirring, and ultrasonicating to obtain a cellulose nanofibril / graphene oxide-silane mixed solution;
[0010] (3) The obtained cellulose nanofibril / graphene oxide-silane mixed solution is transferred to a sealed container, reacted at 25-95° C. for 15-75 hours, and then solvent replacement washing and drying at room temperature and pressure are performed to obtain cellulose nanofibril / graphene oxide-silicon-based composite aerogel, that is, the cellulose nanofibril / graphene oxide modified thermal insulation and flame retardant silicon-based composite aerogel.
[0011] Furthermore, the weight parts of the main raw materials for preparing the composite aerogel are: 10 to 35 parts of silane coupling agent, 0.001 to 0.08 parts of acid catalyst, 0.1 to 6 parts of surfactant, 0.5 to 12 parts of co-solvent, 10 to 75 parts of water, 5 to 25 parts of base catalyst, and 1 to 10 parts of cellulose nanofibril / graphene oxide co-grinding solution.
[0012] Furthermore, the silane coupling agent is a mixture of trialkoxysilane, dialkoxysilane and trialkoxy fluorine-containing silane in a mass ratio of 5-25:5-12:1-10.
[0013] Furthermore, the trialkoxysilane is at least one selected from methyltrimethoxysilane, ethyltrimethoxysilane, methyltriethoxysilane, and ethyltriethoxysilane.
[0014] Furthermore, the bisalkoxysilane is at least one selected from dimethyldimethoxysilane, ethyldimethoxysilane, and ethyldiethoxysilane.
[0015] Furthermore, the trialkoxy fluorine-containing silane is at least one selected from aminopropylmethyldimethoxysilane, nonafluorohexyltrimethoxysilane, perfluorooctyltrimethoxysilane, and perfluorodecyltrimethoxysilane.
[0016] Furthermore, the acid catalyst is at least one selected from acetic acid, hydrochloric acid, nitric acid, and citric acid; the introduction of the acid can construct an acidic reaction environment and induce the hydrolysis process of the siloxy groups on the silane.
[0017] Furthermore, the surfactant is at least one selected from hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, dodecyldimethylbenzylammonium chloride, and octadecyltrimethylammonium chloride; the surfactant molecules are adsorbed on the surface and interface of the system, thereby greatly changing the interfacial energy, which is beneficial to promoting the hydrolysis condensation reaction of the silane precursor.
[0018] Furthermore, the co-solvent is at least one selected from methanol, ethanol, ethylene glycol, n-octane, n-octanol, p-xylene, and o-xylene. The co-solvent can provide sufficient hydroxyl groups to increase the concentration of hydroxyl groups, thereby affecting the reaction kinetics and facilitating the hydrolysis condensation process.
[0019] Furthermore, the alkaline catalyst is at least one selected from sodium hydroxide, potassium hydroxide, urea, ammonia water, and tetramethylammonium hydroxide, and its function is to promote the polycondensation of silanol groups.
[0020] Furthermore, the preparation operation of the cellulose nanofibril / graphene oxide co-grinding solution is as follows: cellulose is chemically pretreated with a pretreatment reagent, and then a graphene oxide aqueous solution with different solute masses is added, and after stirring evenly, the cellulose nanofibril / graphene oxide co-grinding solution is prepared by mechanical grinding with an ultrafine grinder.
[0021] Furthermore, based on the cellulose solute mass, a certain solute mass ratio of graphene oxide aqueous solution was weighed, and the mass ratio of the two fillers, cellulose and graphene oxide, was 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, and 1:9 (here is the weight ratio of pretreated cellulose and graphene oxide in the solution before co-grinding).
[0022] Furthermore, the pretreatment reagent is selected from a borate reagent, a sulfonate reagent, and a phosphorylation reagent; for example, the borate reagent includes sodium tetraborate, borax, boric acid, etc., and the sulfonate reagent mainly includes SO 3 , concentrated sulfuric acid, fuming sulfuric acid, chlorosulfonic acid, sulfite, etc. The phosphating reagents include potassium dihydrogen phosphate, sodium dihydrogen phosphate, diammonium hydrogen phosphate, etc.
[0023] Furthermore, the cellulose is at least selected from bamboo powder, bamboo-based fiberboard, and palm fiber.
[0024] Furthermore, the cellulose is chemically pretreated with a pretreatment agent, and its specific treatment steps include: flocculating and washing the cellulose raw material through a grinder to remove soluble impurities in the fiber, and then placing it in a blast oven to dry to remove excess moisture; after the fiber is constant weight, taking the fiber and placing it in deionized water for swelling and soaking; then adding urea and pretreatment agents to the suspension, mechanically stirring and dissolving it, and then placing the suspension in a blast oven to dry; after the pretreatment agent / fiber mixture is constant weight, high temperature curing treatment is performed; and the treated fiber is fully washed with deionized water until it is neutral.
[0025] Furthermore, in step (3), the solvent replacement washing is carried out in two steps. The first step uses an organic solvent, specifically at least one selected from ethanol, octanol and isopropanol, to wash away unreacted raw materials; the second step uses a low surface tension solvent, specifically at least one selected from n-hexane, n-heptane and n-octane, which is inexpensive and has a low surface energy. After washing, the aerogel can maintain a stable skeleton during the normal pressure drying process.
[0026] The cellulose nanofibril / graphene oxide modified heat-insulating flame-retardant silicon-based composite aerogel obtained in the present application has a density of 86 mg / cm -3 .
[0027] The present application also provides an application of the thermal insulation and flame retardant silicon-based composite aerogel modified with cellulose nanofibrils / graphene oxide prepared by the above method in the field of thermal insulation.
[0028] Advantages and beneficial effects of this application:
[0029] 1. The cellulose nanofibrils / graphene oxide in this application are novel nanofillers prepared by chemical pretreatment combined with mechanical grinding, which have the following advantages: First, functionalized cellulose nanofibrils and graphene oxide can effectively inhibit aggregation, because they are rich in hydrophilic groups (such as hydroxyl groups) and have good water dispersibility; therefore, the nanofillers can be evenly dispersed in the covalently cross-linked three-dimensional skeleton network to form dynamic physical interactions, such as hydrogen bonds, thereby improving the mechanical properties and enhancing the organic silicon network structure. The research results show that the mechanical properties of the obtained aerogel are indeed greatly improved, which confirms the enhancement effect of cellulose nanofibrils / graphene oxide; secondly, the addition of graphene oxide greatly improves the flame retardancy of silicon-based aerogels, and forms a synergistic flame retardant effect with functionalized nanofibrils. In the aerogel, the functionalized groups form electrostatic interactions with the oxygen-containing groups in graphene oxide, generate bridge connections, and promote the interconnection between adjacent graphene oxides, thereby establishing a reliable three-dimensional network skeleton; therefore, this nanofiller composite aerogel has a good balance of mechanical and flame retardant properties.
[0030] 2. The aerogel of the present application, wherein the hydrogen bonds and π-π stacking between the graphene oxide sheets and functionalized nanofibrils reduce the void diameter and limit the convective heat transfer of the air; on the other hand, the resulting micro-nanopores can also effectively inhibit solid heat transfer, and the unique three-dimensional network structure makes the solid heat conduction path inside the aerogel "infinitely elongated", and the heat is infinitely consumed in the conduction path; thereby improving the thermal insulation performance of the material; in summary, the cellulose nanofibril / graphene oxide modified silicon-based composite aerogel prepared in the present application not only has superior mechanical properties, but also has excellent flame retardancy and high and low temperature thermal insulation, and is suitable for market promotion and application.
[0031] 3. The technical solution of the present application adopts a co-solvent. The mechanical properties of the aerogel mainly depend on its network structure, which can be controlled by co-solvents of different polarities (such as alcohols, alkanes and aromatics). The influence on the network structure is achieved by changing the hydrolysis and polycondensation reactions of silane in the sol-gel and phase separation processes. The present application can promote a hydrolysis and polycondensation reaction of silane by adding a specific type and amount of co-solvent to enhance its network structure; in addition, the subsequently introduced cellulose nanofibrils / graphene oxide have a strong electrostatic effect with the surfactant, which can easily cause the collapse of the aerogel network. The co-solvent added here can better introduce the cellulose nanofibrils / graphene oxide reinforcement phase to avoid collapse.
[0032] 4. The technical solution of the present application forms a silane coupling agent through three specific types of substances. The CF bond energy in the trialkyl fluorinated siloxane compound is large, the intermolecular force is small, and the surface energy is very low, which can increase the hydrophobicity of the aerogel. The solution of modifying the precursor using three silane coupling agents in the present application can not only improve the mechanical properties of the aerogel network structure, but also give it excellent hydrophobicity.
[0033] 5. Cellulose nanoderivatives can enhance the mechanical properties of aerogels. However, due to the surface inertness, cellulose nanoderivatives cannot form strong and effective interactions with the matrix, which limits the full play of their excellent mechanical properties and causes the mechanical enhancement effect to be limited to a certain extent. This is because traditional cellulose nanofibrils have strong hydrogen bonds between the fibrils that are difficult to break, and are therefore not easy to disperse. Among them, the single hydroxyl functional group limits the widespread use of cellulose. After the chemical pretreatment of the present application, the cellulose surface has functional groups, and compared with untreated cellulose, it has a higher aspect ratio, better water dispersibility and a better degree of nano-sizing, which provides more possibilities for constructing internal interactions in the aerogel system.
[0034] 6. The present application constructs a strong skeleton structure by utilizing the high mechanical properties of nanofibrils / graphene oxide, the nanometer size and the high polarity of the surface, and can simultaneously form multiple interactions (covalent bonds, chemical bonds and hydrogen bonds) with silane molecules, thereby improving the mechanical properties of the composite aerogel; therefore, the cellulose nanofibrils / graphene oxide modified insulating and flame-retardant silicon-based composite aerogel prepared by the present application not only has excellent mechanical properties, but also has excellent flame retardancy and high-temperature thermal insulation. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a digital photo of the modified aerogel sample prepared in Example 3.
[0036] Figure 2 The following is a photograph showing the compression recovery performance of the modified aerogel sample prepared in Example 3.
[0037] Figure 3 These are combustion comparison test photos of the unmodified aerogel sample A prepared in comparative example 1 and the modified aerogel sample B prepared in example 3.
[0038] Figure 4 The stress-strain curves of the modified aerogel sample prepared in Example 3 and the unmodified aerogel sample prepared in Comparative Example 1 under 50% compressive strain.
[0039] Figure 5 This is a thermal imaging infrared image of the modified aerogel sample prepared in Example 3 on a 300°C heating table.
[0040] Figure 6 The graph shows the change of the surface temperature of the top area of the modified aerogel sample prepared in Example 3 with time under heating platforms of different temperatures.
[0041] Figure 7 This is a thermal imaging infrared image of the modified aerogel sample prepared in Example 3 placed on an ice pack at -9°C for 1200 seconds. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0043] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this application are performed using conventional test methods in the art. It should be understood that the terms described in this application are only used to describe specific implementation methods and are not used to limit the content disclosed in this application.
[0044] Unless otherwise specified, the technical and scientific terms used in this document have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs; other experimental methods and technical means not specifically specified in this application refer to experimental methods and technical means commonly used by ordinary technicians in this field.
[0045] In order to better illustrate the content of the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present application.
[0046] Under the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present application.
[0047] In order to better understand the present application, the present application is further specifically described below through the following embodiments, but it should not be understood as a limitation of the present application. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the scope of protection of the present application.
[0048] The cellulose nanofibril / graphene oxide co-grinding solution of the present application has the following specific steps: flocculating and washing the cellulose raw material through a grinder to remove soluble impurities in the fiber, and then placing it in a blast oven to dry to remove excess water; after the fiber is constant in weight, taking the fiber and placing it in deionized water for swelling and soaking; then adding urea and a pretreatment agent to the suspension, mechanically stirring and dissolving it, and then placing the suspension in a blast oven to dry; after the pretreatment agent / fiber mixture is constant in weight, high-temperature curing treatment is performed; the treated cellulose is fully washed with deionized water to neutrality, and then a certain mass ratio of graphene oxide aqueous solution is weighed based on the mass of cellulose, and added to the cellulose just washed to neutrality; next, the cellulose, graphene oxide and deionized water are prepared into a suspension of a certain concentration, and ground by an ultrafine grinder to obtain a uniform cellulose nanofibril / graphene oxide co-grinding solution.
[0049] Embodiment 1
[0050] 15g of methyltrimethoxysilane, 10g of ethyldimethoxysilane, 1.05g of perfluorodecyltrimethoxysilane, 0.03g of hydrochloric acid, 5g of hexadecyltrimethylammonium chloride, 60g of water and 10g of ethylene glycol were added to a beaker in sequence, and magnetic stirring was performed for 30min to fully hydrolyze the silane; then 10g of ammonia water was added to the hydrolyzed solution, and vigorously stirred for 10min; thereafter, 1g of cellulose nanofibrils (bamboo powder chemically pretreated with boric acid reagent) / graphene oxide co-grinding solution was taken and added to the silica sol solution, and fully stirred and ultrasonically treated for 5min; the treated solution was poured into a mold, sealed, and placed in an oven at 90°C for 60h, the modified silicon wet gel that had reacted was taken out, and solvent replacement was performed in ethanol and n-octane in sequence, and each solvent was replaced three times, and each replacement was 10h. After the replacement was completed, the cellulose nanofibrils / graphene oxide modified heat-insulating flame-retardant silicon-based composite aerogel was obtained by drying at room temperature and pressure.
[0051] Embodiment 2
[0052] 4 g of methyltriethoxysilane, 2 g of ethyldiethoxysilane, 0.21 g of nonafluorohexyltrimethoxysilane, 0.006 g of nitric acid, 0.6 g of octadecyltrimethylammonium chloride, 18 g of water and 0.6 g of p-xylene were added to a beaker in sequence and magnetically stirred for 30 min to fully hydrolyze the silane; then 6 g of sodium hydroxide was added to the hydrolyzed solution and vigorously stirred for 10 min; then 2 g of cellulose nanofibrils (bamboo powder chemically pretreated with sulfonated reagent) / graphene oxide co-grinding solution was taken and added to the silica sol solution, fully stirred and ultrasonically treated for 5 min; the treated solution was poured into a mold, sealed and placed in an oven at 30°C for 20 h, the modified silicon wet gel that had reacted was taken out, and solvents were replaced in octanol and n-heptane in sequence, each solvent was replaced three times, and each replacement lasted 10 h. After the replacement was completed, the cellulose nanofibrils / graphene oxide modified heat-insulating flame-retardant silicon-based composite aerogel was obtained by drying at room temperature and pressure.
[0053] Embodiment 3
[0054] 3 g of methyltrimethoxysilane, 2 g of dimethyldimethoxysilane, 0.21 g of perfluorooctyltrimethoxysilane, 0.005 g of acetic acid, 0.8 g of hexadecyltrimethylammonium bromide, 15 g of water and 1.5 g of o-xylene were added to a beaker in sequence, and magnetic stirring was performed for 30 min to fully hydrolyze the silane; 5 g of urea was then added to the hydrolyzed solution, and vigorously stirred for 10 min; 2 g of cellulose nanofibrils (bamboo-based fiberboard chemically pretreated with phosphorylation reagent) / graphene oxide co-grinding solution was then taken and added to the silica sol solution, and fully stirred and ultrasonically treated for 5 min; the treated solution was poured into a mold, sealed, and placed in an oven at 80°C for 48 h, the modified silicon wet gel that had reacted was taken out, and solvents were replaced in isopropanol and n-hexane in sequence, each solvent was replaced three times, and each replacement lasted for 10 h. After the replacement was completed, the cellulose nanofibrils / graphene oxide modified heat-insulating flame-retardant silicon-based composite aerogel was obtained by drying at room temperature and pressure.
[0055] Embodiment 4
[0056] 9 g of ethyltrimethoxysilane, 6.3 g of ethyldimethoxysilane, 0.63 g of triaminopropylmethyldimethoxysilane, 0.0075 g of citric acid, 1.5 g of dodecyldimethylbenzyl ammonium chloride, 30 g of water and 2.25 g of methanol were added to a beaker in sequence, and magnetic stirring was performed for 30 min to fully hydrolyze the silane; then 12 g of tetramethylammonium hydroxide was added to the hydrolyzed solution, and vigorously stirred for 10 min; then 3 g of cellulose nanofibrils (bamboo-based fiberboard chemically pretreated with borate reagent) / graphene oxide co-grinding liquid was taken, added to the silica sol solution, and fully stirred and ultrasonically treated for 5 min; the treated solution was poured into a mold, sealed, and placed in an oven at 70°C for 50 h, the modified silicon wet gel that had reacted was taken out, and solvent replacement was performed in ethanol and n-hexane in sequence, each solvent was replaced three times, and each replacement was 8 h. After the replacement was completed, the cellulose nanofibrils / graphene oxide modified heat-insulating flame-retardant silicon-based composite aerogel was obtained by drying at room temperature and pressure.
[0057] Embodiment 5
[0058] 6.75 g of methyltriethoxysilane, 4.5 g of ethyldiethoxysilane, 0.45 g of perfluorooctyltrimethoxysilane, 0.008 g of hydrochloric acid, 2.25 g of hexadecyltrimethylammonium chloride, 37.5 g of water and 3.75 g of n-octanol were added to a beaker in sequence, and magnetic stirring was performed for 30 min to fully hydrolyze the silane; then 7.5 g of sodium hydroxide was added to the hydrolyzed solution, and vigorously stirred for 10 min; then 4 g of cellulose nanofibrils (brown fibers chemically pretreated with sulfonated reagent) / graphene oxide co-grinding liquid was taken, added to the silica sol solution, and fully stirred and ultrasonically treated for 5 min; the treated solution was poured into a mold, sealed, and placed in an oven at 45°C for 36 h, the modified silicon wet gel that had reacted was taken out, and solvents were replaced in octanol and n-hexane in sequence, each solvent was replaced three times, and each replacement was 8 h. After the replacement was completed, the cellulose nanofibrils / graphene oxide modified heat-insulating flame-retardant silicon-based composite aerogel was obtained by drying at room temperature and pressure.
[0059] Embodiment 6
[0060] 2g of ethyltriethoxysilane, 1g of dimethyldimethoxysilane, 0.2g of aminopropylmethyldimethoxysilane, 0.006g of nitric acid, 1.2g of dodecyldimethylbenzyl ammonium chloride, 12g of water and 0.9g of p-xylene were added to a beaker in sequence and magnetically stirred for 30min to fully hydrolyze the silane; then 4.5g of ammonia water was added to the hydrolyzed solution and vigorously stirred for 10min; then 1g of cellulose nanofibrils (brown fibers chemically pretreated with phosphorylation reagent) / graphene oxide co-grinding liquid was taken and added to the silica sol solution, fully stirred and ultrasonically treated for 5min; the treated solution was poured into a mold, sealed and placed in an oven at 60°C for 50h, the modified silicon wet gel was taken out and solvent replaced in isopropanol and n-heptane in sequence, each solvent was replaced three times, each replacement was 8h, and after the replacement was completed, the cellulose nanofibrils / graphene oxide modified heat-insulating flame-retardant silicon-based composite aerogel was obtained by drying at room temperature and pressure.
[0061] Embodiment 7
[0062] 3.15 g of methyltriethoxysilane, 2.1 g of ethyldiethoxysilane, 0.21 g of nonafluorohexyltrimethoxysilane, 0.0165 g of acetic acid, 1.65 g of hexadecyltrimethylammonium bromide, 27.5 g of water, and 4.4 g of p-xylene were added to a beaker in sequence, and magnetic stirring was performed for 30 min to fully hydrolyze the silane; then 8.25 g of urea was added to the hydrolyzed solution, and vigorously stirred for 10 min; then cellulose nanofibrils (chemically prepared with borate reagent) were taken out and the mixture was stirred for 10 min. 2g of treated brown fiber) / graphene oxide co-grinding liquid is added to the silica sol solution, stirred thoroughly and ultrasonically treated for 5 minutes; the treated solution is poured into a mold, sealed, and placed in a 65°C oven for 54 hours, the modified silica wet gel is taken out, and solvents are replaced in isopropanol and n-octane in turn, each solvent is replaced three times, each replacement is 8 hours, and after the replacement is completed, the cellulose nanofibrils / graphene oxide modified heat-insulating flame-retardant silicon-based composite aerogel is obtained by drying at room temperature and pressure.
[0063] Embodiment 8
[0064] 3 g of ethyltrimethoxysilane, 2 g of ethyldiethoxysilane, 0.21 g of perfluorooctyltrimethoxysilane, 0.005 g of acetic acid, 0.6 g of dodecyldimethylbenzyl ammonium chloride, 15 g of water and 1.5 g of p-xylene were added to a beaker in sequence, and magnetic stirring was performed for 30 min to fully hydrolyze the silane; 5 g of urea was then added to the hydrolyzed solution and stirred vigorously for 10 min; 5 g of cellulose nanofibrils (bamboo powder chemically pretreated with sulfonated reagent) / graphene oxide co-grinding liquid was then taken and added to the silica sol solution, fully stirred and ultrasonically treated for 5 min; the treated solution was poured into a mold, sealed, and placed in an oven at 50°C for 40 h, the modified silicon wet gel that had reacted was taken out, and solvents were replaced in isopropanol and n-hexane in sequence, each solvent was replaced three times, and each replacement was 8 h. After the replacement was completed, the cellulose nanofibrils / graphene oxide modified heat-insulating flame-retardant silicon-based composite aerogel was obtained by drying at room temperature and pressure.
[0065] Comparative Example 1
[0066] 3 g of methyltrimethoxysilane, 2 g of dimethyldimethoxysilane, 0.21 g of perfluorooctyltrimethoxysilane, 0.005 g of acetic acid, 0.8 g of hexadecyltrimethylammonium bromide, 15 g of water and 1.5 g of o-xylene were added into a beaker in sequence and stirred magnetically for 30 min to fully hydrolyze the silane; then 5 g of urea was added into the hydrolyzed solution and stirred vigorously for 10 min; the treated solution was poured into a mold, sealed and placed in an oven at 80°C for 48 h; then the silicon wet gel after the reaction was taken out and solvent replaced in isopropanol and n-hexane in sequence, each solvent was replaced three times, each replacement lasting 10 h, and after the replacement was completed, the unmodified silicon-based aerogel was obtained by drying at room temperature and pressure.
[0067] See attached Figure 1 This is a digital photo of the modified aerogel prepared in Example 3 of the present application, which can be placed on a flower and exhibits a low-density characteristic, with a density of 86 mg / cm -3 .
[0068] See attached Figure 2 This is a digital photo showing the compression recovery performance of the modified aerogel prepared in Example 3 of this application. Figure 3 It can be seen that the aerogel can be compressed at a high compression rate under a 1Kg weight pressure and recover quickly after release, which shows that it has excellent flexibility and further confirms its excellent and balanced mechanical properties.
[0069] See attached Figure 3 The following are the combustion comparison test photos of the unmodified aerogel sample A prepared in Example 1 and the modified aerogel sample B prepared in Example 3. Figure 3It can be seen that the unmodified aerogel A started to burn 2 seconds after contact with the flame, and continued to burn after leaving the flame without self-extinguishing. During the combustion process, the network skeleton gradually thermally decomposed and shrank; while the modified aerogel B showed very excellent flame retardant properties. After being attacked by the flame of the alcohol lamp for 1 minute, there was no phenomenon of flame diffusion and spread. After leaving the flame, there was a phenomenon of self-extinguishing and the morphology remained good without obvious damage.
[0070] See attached Figure 4 The stress-strain curves of the aerogels prepared in Comparative Example 1 and Example 3 under 50% compressive strain are shown in FIG. Figure 4 It can be seen that the aerogel prepared in Example 3 has excellent and balanced mechanical properties, and its compressive strength is 43.66 kPa, which is 244% higher than the compressive strength (12.68 kPa) of the unmodified aerogel in Comparative Example 1. This shows that the presence of the functionalized cellulose nanofibril / graphene oxide co-grinding filler can further improve the mechanical properties of the silicon-based aerogel.
[0071] See attached Figure 5 This is a thermal imaging infrared image of the modified aerogel prepared in Example 3 of the present application placed on a 300°C heating plate for 15 minutes; see Attachment Figure 6 is a graph showing the temperature of the top area of the modified aerogel prepared in Example 3 of the present application changing with time on heating plates at different temperatures, Figure 5 and 6 It can be seen that the composite aerogel has excellent thermal insulation performance (the thermal insulation temperature is >220℃ when eroded at 300℃); see Appendix Figure 7 This is a thermal imaging infrared image of the modified aerogel synthesized in Example 3 of the present application placed on a -9°C ice pack for 20 minutes. Figure 7 It can be seen that the aerogel has excellent cold insulation performance, which makes the aerogel prepared in the present application have broad application prospects in the field of high and low temperature (-9°C-300°C) thermal insulation.
[0072] The drawings in the above description are merely embodiments of the present application. A person skilled in the art can obtain other drawings based on the provided drawings without any creative effort.
[0073] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a heat-insulating flame-retardant silicon-based composite aerogel, characterized in that: The specific steps include: (1) mixing a silane coupling agent, an acid catalyst, a surfactant, a co-solvent and water, adjusting the pH to 2 to 5, stirring and hydrolyzing to obtain a silica sol solution; (2) adding an alkali catalyst to the obtained silica sol solution, stirring, adjusting the pH to 9-11, adding a cellulose nanofibril / graphene oxide co-grinding solution, stirring, and ultrasonicating to obtain a cellulose nanofibril / graphene oxide-silane mixed solution; (3) The obtained cellulose nanofibril / graphene oxide-silane mixed solution is transferred to a sealed container, reacted at 25-95° C. for 15-75 hours, and then solvent replacement washing and drying at room temperature and pressure are performed to obtain cellulose nanofibril / graphene oxide-silicon-based composite aerogel, that is, the cellulose nanofibril / graphene oxide modified thermal insulation and flame retardant silicon-based composite aerogel.
2. The method for preparing the heat-insulating flame-retardant silicon-based composite aerogel according to claim 1, characterized in that: The weight parts of the main preparation raw materials in step (1) and step (2) are: 10 to 35 parts of silane coupling agent, 0.001 to 0.08 parts of acid catalyst, 0.1 to 6 parts of surfactant, 0.5 to 12 parts of co-solvent, 10 to 75 parts of water, 5 to 25 parts of base catalyst, and 1 to 10 parts of cellulose nanofibril / graphene oxide co-grinding solution.
3. The method for preparing the heat-insulating flame-retardant silicon-based composite aerogel according to claim 2, characterized in that: The silane coupling agent is a mixture of trialkoxysilane, dialkoxysilane and trialkoxy fluorine-containing silane in a mass ratio of 5-25:5-12:1-10.
4. The method for preparing the heat-insulating flame-retardant silicon-based composite aerogel according to claim 3, characterized in that: The trialkoxysilane is at least selected from one of methyltrimethoxysilane, ethyltrimethoxysilane, methyltriethoxysilane, and ethyltriethoxysilane; the dialkoxysilane is at least selected from one of dimethyldimethoxysilane, ethyldimethoxysilane, and ethyldiethoxysilane; the trialkoxy fluorine-containing silane is at least selected from one of aminopropylmethyldimethoxysilane, nonafluorohexyltrimethoxysilane, perfluorooctyltrimethoxysilane, and perfluorodecyltrimethoxysilane.
5. The method for preparing the heat-insulating flame-retardant silicon-based composite aerogel according to claim 2, characterized in that: The acid catalyst is at least one selected from acetic acid, hydrochloric acid, nitric acid and citric acid.
6. The method for preparing the heat-insulating flame-retardant silicon-based composite aerogel according to claim 2, characterized in that: The surfactant is at least one selected from the group consisting of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, dodecyldimethylbenzylammonium chloride and octadecyltrimethylammonium chloride.
7. The method for preparing the heat-insulating flame-retardant silicon-based composite aerogel according to claim 2, characterized in that: The co-solvent is at least one selected from methanol, ethanol, ethylene glycol, n-octane, n-octanol, p-xylene, and o-xylene.
8. The method for preparing the heat-insulating flame-retardant silicon-based composite aerogel according to claim 2, characterized in that: The alkaline catalyst is at least one selected from sodium hydroxide, potassium hydroxide, urea, ammonia water, and tetramethylammonium hydroxide.
9. The method for preparing the heat-insulating flame-retardant silicon-based composite aerogel according to claim 2, characterized in that: The preparation operation of the cellulose nanofibril / graphene oxide co-grinding solution is as follows: cellulose is chemically pretreated with a pretreatment reagent, and then graphene oxide aqueous solutions with different solute masses are added, stirred evenly, and then mechanically ground with an ultrafine grinder to prepare the cellulose nanofibril / graphene oxide co-grinding solution.
10. The method for preparing the heat-insulating flame-retardant silicon-based composite aerogel according to claim 9, characterized in that: Based on the cellulose solute mass, a graphene oxide aqueous solution with a certain solute mass ratio was weighed. The mass ratios of the two fillers, cellulose and graphene oxide, were 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, and 1:
9.
11. The method for preparing the heat-insulating flame-retardant silicon-based composite aerogel according to claim 9, characterized in that: The pretreatment reagent is selected from a boration reagent, a sulfonation reagent, and a phosphorylation reagent.
12. The method for preparing the heat-insulating flame-retardant silicon-based composite aerogel according to claim 11, characterized in that: The boration agent is at least one of sodium tetraborate, borax, and boric acid; the sulfonation agent mainly includes at least one of SO3, concentrated sulfuric acid, oleum, chlorosulfonic acid, and sulfite; and the phosphorylation agent is at least one of potassium dihydrogen phosphate, sodium dihydrogen phosphate, and diammonium hydrogen phosphate.
13. The method for preparing the heat-insulating flame-retardant silicon-based composite aerogel according to claim 9, characterized in that: The cellulose is at least selected from bamboo powder, bamboo-based fiberboard and palm fiber.
14. The method for preparing the heat-insulating flame-retardant silicon-based composite aerogel according to claim 9, characterized in that: The cellulose is chemically pretreated with a pretreatment agent, and its specific treatment steps include: flocculating and washing the cellulose raw material through a grinder to remove soluble impurities in the fiber, and then placing it in a blast oven to dry to remove excess moisture; after the fiber is constant in weight, taking the fiber and placing it in deionized water for swelling and soaking; then adding urea and the pretreatment agent to the suspension, mechanically stirring and dissolving, and then placing the suspension in a blast oven to dry; after the pretreatment agent / fiber mixture is constant in weight, high-temperature curing treatment is performed; and the treated fiber is fully washed with deionized water until it is neutral.
15. The method for preparing the heat-insulating flame-retardant silicon-based composite aerogel according to any one of claims 1 to 14, characterized in that: The density of the prepared aerogel is 86 mg / cm -3 .
16. The method for preparing the heat-insulating flame-retardant silicon-based composite aerogel according to claim 15, characterized in that: In step (3), the solvent replacement washing is carried out in two steps. The first step uses an organic solvent, specifically at least one selected from ethanol, octanol and isopropanol, to wash away unreacted raw materials; the second step uses a low surface tension solvent, specifically at least one selected from n-hexane, n-heptane and n-octane.
17. Use of a thermal insulation and flame retardant silicon-based composite aerogel modified with cellulose nanofibrils / graphene oxide prepared by the method according to any one of claims 1 to 14 in the field of thermal insulation.
Citation Information
Patent Citations
Fiber-reinforced heat-insulating silicone aerogel composite material and preparation method thereof
CN108641361A
A method for preparing graphene oxide modified flame-retardant silica aerogel
CN110127705B
A biomass fiber reinforced organosilicon aerogel composite material, its preparation method and application
CN111560172B
Preparation method of graphene oxide-modified flame retardant silica aerogel
CN110127705A
Cellulose nanofibril modified heat-insulating silicon-based composite aerogel as well as preparation method and application thereof
CN117164942A
Cited By
High-toughness thermal bridge blocking material and preparation method thereof
CN121181334A
A high-toughness thermal bridge breaking material and a preparation method thereof
CN121181334B